Terapia de aceptación y compromiso y miedo a la recurrencia del cáncer: una revisión aplicada - Argote Olortegui, Nikole Alexandra (2023)
Most post-treatment cancer survivors manifest Fear of Cancer Recurrence (FCR), a variable that affects the social, work, economic and personal area. Therefore, the importance of evaluating a psychological intervention compatible with the FCR is highlighted. We proposed as an objective to study the relationship between Acceptance and Commitment Therapy (ACT) and FCR in cancer survivors older than 18 years through an applied review. A search was carried out in the Scopus, SpringerLink, ScienceDirect and Web of Science databases to identify the most pertinent investigations, of which 10 studies were selected, whose study designs were experimental and longitudinal, except for one nonexperimental and cross-sectional research. The results demonstrated a significant negative relationship between the variables, such that, in most studies, the ACT decreased the FCR. In conclusion, an improvement in the FCR was identified using ACT. This emphasizes the implication of the study, which details that the survivors optimized their quality of life. Regarding the limitations, there was little literature regarding the problem and a varied inclusion of eligibility criteria in the samples and measurement instruments.